A rare case of late chromophobe RCC metastasis with indolent course - Anastasiou, Periklis; Douroumis, Konstantinos; Panagopoulos, Panagiotis; Katsikatsos, Panagiotis; Kalfountzos, Christos; Davakis, Spyridon; Anastasiou, Ioannis (Urology case reports, 2025)
Renal cell carcinoma (RCC) is the predominant solid lesion of the kidney. Among the various subtypes of RCC, chromophobe RCC (chRCC) is relatively rare, and it is characterized by an indolent clinical course and a favourable prognosis. We present a rare case of a 40-year-old patient who developed a retroperitoneal metastasis four years after undergoing radical nephrectomy for chRCC. The patient was under surveillance for another six years before surgical excision of the recurrence was performed. This case underscores the potential for late recurrence in chRCC and highlights the importance of long-term surveillance, even in patients with an initially favourable prognosis.